(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Background: Chronic Kidney disease is becoming a global public health problem throughout the world. Objective: The aim of the study was to assess the management status of hemodialysis unit for care receivers in a specialized hospital. Methodology: This was a hospital based descriptive cross-sectional study. The participants were selected by purposive sampling method on the basis of defined selection criteria from January 2015 to December 2016. The place of study was National Institute of Kidney Diseases and Urology (NIKDU) hospital, Dhaka. The research instruments were a semi structured questionnaire and an observational checklist. Data were collected from respondents by face to face interview and an observational Checklist was also used to collect information regarding administrative facility, physical facility and utility services. Result: The findings of the study were presented by frequency, percentage in tables. Means and standard deviations for continuous variables and frequency distributions for categorical variables were used to describe the characteristics of the total sample. Among the service receiver, mean age was 46.65±13.53 years of which 69.9 %( n=58) were male and their average monthly income Tk. 20670±14811. Formalin and hydrogen per oxide were used to wash dialyzer. In the support services unit, equipment and stationery were supplied always. Ratio of health care receiver and provider in the unit was Patient-doctor ratio 1:15 and Patient-nurse ratio 1:6. From the respondents 38 (45.8%) said that, doctor/ nurse visit them thrice per cycle. In majority of respondents, were satisfied regarding the unit including doctors and nurses activities, physical facilities, and cleanliness of the unit, except the cleanliness of toilet. Conclusion: Increasing number of functioning dialysis machine, skilled manpower, medicine supply and strict infection control measure could be helpful to improve the management status of the hemodialysis unit of NIKDU. Bangladesh Journal of Infectious Diseases 2020;7(2):84-89